Cultura de embrião e indução de brotos in vitro para micropropagação do pinhão-manso - Lopes, Leandro Cesar [UNESP]; Machado, Isaac Stringueta [UNESP]; Magoga, Elaine Cristina [UNESP]; Andrade, Juliana Granito de [UNESP]; Penna, Henrique Curi [UNESP]; Moraes, Lucas Eduardo Fischer [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2012)
O objetivo deste trabalho foi otimizar o cultivo e desenvolvimento de embriões, bem como avaliar a indução da micropropagação do pinhão-manso (Jatropha curcas) in vitro. Na primeira etapa, foi avaliada a influência da sacarose (concentrações 0, 15, 30 e 60 g L-1) no desenvolvimento de embriões em meio basal MS. Das plântulas geradas no cultivo de embriões, foram excisadas microestacas e colocadas em meio MS suplementado com os reguladores vegetais 6-benziladenina (BA), 6-benzilaminopurina (BAP), cinetina (6-furfuriladenina) (KIN) e ácido 4-(3-indolil) butírico (AIB), nas concentrações 0,5, 1,0, 2,0 e 3,0 mg L-1. Os resultados evidenciaram que a faixa de 15 a 30 g L-1 de suplementação exógena da sacarose promove o melhor alongamento da parte aérea das plantas; a rizogênese, contudo, é mais vigorosa na faixa de 30 a 60 g L-1, em que ocorre aumento significativo do número de raízes. Na fase de micropropagação, o BAP à concentração de 2,0 mg L-1 induz maior número de brotações, enquanto a KIN (1,0 e 2,0 mg L-1) promove maior número de folhas. Ocorre calogênese na base das brotações, mais significativa na suplementação com 2,0 mg L-1 de 6-BAP. A melhor concentração de sacarose, quanto ao vigor vegetal e rapidez na obtenção de explantes, é de 30 g L-1. Na micropropagação, os melhores resultados da organogênese direta de brotações ocorrem à concentração de 2,0 mg L-1 de BAP.

The objective of this work was to optimize the cultivation and embryo development, as well as to evaluate in vitro micropropagation induction of physic nut (Jatropha curcas). In the initial stage, the influence of sucrose (concentrations of 0, 15, 30 and 60 g L-1) on the development of embryos in basal MS medium was evaluated. From the seedlings generated in the embryo culture, microcuttings were excised and inoculated on MS medium supplemented with the plant regulators 6-benzyladenine (BA), 6-benzylaminopurine (BAP), kinetin (6-furfuryladenine) (KIN) and 4-(3-indolyl) butyric acid (IBA), in the concentrations of 0.5, 1.0, 2.0 and 3.0 mg L-1. The results showed that the range of 15 to 30 g L-1 of exogenous supplementation with sucrose promotes the best shoot elongation of plants; however, rhizogenesis is more vigorous in the range from 30 to 60 g L-1, in which a significant increase of the number of roots occurs. In the micropropagation phase, BAP at 2.0 mg L-1 concentration induces a higher number of shoots, while KIN (1.0 and 2.0 mg L-1) promotes a higher number of leaves. Callogenesis occurs on the shoot base, being more significant when supplemented with 2.0 mg L-1 of 6-BAP. The best sucrose concentration, for plant vigor and speed in obtaining explants, is 30 g L-1. In micropropagation, the best results for direct shoot organogenesis occur at 2.0 mg L-1 BAP concentration.
Embryo culture and in vitro induction of shoots for micropropagation of physic nut
Keywords: Jatropha curcas; auxinas; citocininas; germinação in vitro; organogênese; sacarose; Jatropha curcas; auxins; cytokinins; in vitro germination; organogenesis; sucrose